CONTROL SYSTEM ANALYSIS, MOBILE PHONE MARKETING IN PT SENTRA PRIMA ASKARA - Suwarno Suwarno; Sutarno Sutarno, S.Kom., MMSI (Jurnal Sistem Informasi, 1997)
System can be said to be good if it can need to effectively and efficiently as possible, the analysis of an information system is indispensable for the development of the future. Marketing system at a company are very important, because the marketing will be good or bad menunjuukan products produced by companies bagik consumers.